The origin of glutamatergic synaptic inputs controls synaptic plasticity and its modulation by alcohol in mice nucleus accumbens - Ji, Xincai; Saha, Sucharita; Martin, Gilles E. (Frontiers in Synaptic Neuroscience, 2015)
It is widely accepted that long-lasting changes of synaptic strength in the nucleus accumbens, a brain region involved in drug reward, mediate acute and chronic effects of alcohol. However, our understanding of the mechanisms underlying the effects of alcohol on synaptic plasticity is limited by the fact that the nucleus accumbens receives glutamatergic inputs from distinct brain regions (e.g. the prefrontal cortex, the amygdala and the hippocampus), each region providing different information (e.g. spatial, emotional and cognitive). Combining whole-cell patch-clamp recordings and the optogenetic technique, we examined synaptic plasticity, and its regulation by alcohol, at cortical, hippocampal and amygdala inputs in fresh slices of mouse tissue. We showed that the origin of synaptic inputs determines the basic properties of glutamatergic synaptic transmission, the expression of spike-timing dependent long-term depression (tLTD) and long-term potentiation (tLTP) and their regulation by alcohol. While we observed both tLTP and tLTD at amygadala and hippocampal synapses, we showed that cortical inputs only undergo tLTD. Functionally, we provide evidence that acute EtOH has little effects on higher order information coming from the prefrontal cortex (PFCx), while severely impacting the ability of emotional and contextual information to induce long-lasting changes of synaptic strength.